Replication data for: Threats to cassava production: known and potential geographic distribution of four key biotic constraints - Herrera Campo, Beatriz Vanessa; Hyman, Glenn G.; Bellotti, Anthony C. (2014)
The potential distribution map of the Cassava Greenmite is the result of a weighted overlay combination of several ecological models and a set of environmental variables. Models used were Environmental Distance, Genetic Alrgorithm for Rule-set Production and Support vector Machines. Environmental variables include: Bioclim dataset, number of consecutive dry months, aridity index, potential evapotranspiration and altitude. The potential distribution map of whitefly (Bemisa tabacci) provides a global potential distribution in order to know the places where this species has habitat suitability. The potential distribution map is the result of weighted overlay combination of several ecological models and a set of environmental variables.